Unveiling the Pathogenic Bacteria Causing Descending Necrotizing Mediastinitis - Sun, Qiang; Li, Zixuan; Wang, Panpan; Zhao, Junfang; Chen, Shuai; Sun, Minglei (Frontiers in Cellular and Infection Microbiology, 2022)
The combination of maxillofacial infections (MI) with descending necrotizing mediastinitis (DNM) is a complex disease characterized by rapid development and high mortality. Here, we per-formed metagenomic next-generation sequencing (mNGS) using samples from 21 patients with MI and 8 patients with DNM. In this study, we found that the species richness of the DNM group was higher than that of the MI group, and the species diversity of the DNM group was higher than that of the MI group, with no statistically significant differences between groups (P > 0.05). LefSE analysis revealed that the main species differing between groups were Bacillus, Lactobacillus, Streptococ-caceae, and Streptococcus (S. constellatus and S. anginosus). In addition, the PLS-DA analysis re-vealed that the dominant groups in the DNM group at the species level were: S. constellatus, S. an-ginosus, Streptococcus intermedius, Prevotella oris, Mogibacterium timidum, and Eubacterium no-datum. Next, we correlated the clinical characteristics of the patients with the relative abundance of the pathogens identified in the LefSe and PLS-DA analyses. The relative abundance of S. anginosus was positively correlated with C-reactive protein (CRP) and calcitoninogen (PCT) but negatively correlated with the percentage of lymphocytes (Lymph%) (P < 0.05). On the other hand, M. timidum was positively correlated with the percentage of neutrophils (Neut%) and glycated hemoglobin (GLU) (P < 0.05), and Parvimonas micra was positively correlated with CRP (P < 0.05).